2020
DOI: 10.1007/s40259-020-00443-w
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody-Based Therapies for Myasthenia Gravis

Abstract: Myasthenia gravis (MG) is an autoimmune, neuromuscular disorder that produces disabling weakness through a compromise of neuromuscular transmission. The disease fulfills strict criteria of an antibody-mediated disease. Close to 90% of patients have antibodies directed towards the nicotinic acetylcholine receptor (AChR) on the post-synaptic surface of skeletal muscle and another 5% to the muscle-specific kinase, which is involved in concentrating the AChR to the muscle surface of the neuromuscular junction. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 65 publications
(72 reference statements)
0
18
0
Order By: Relevance
“… 35 Belimumab, a human monoclonal IgG1λ ab directed against B-lymphocyte stimulator (called BLyS, BAFF or TNFSF13B), induces a reduction in B-cell differentiation and thereby leads to a reduced number of circulating CD 19 cells. 37 However, this drug did not show a significant positive effect as adjunctive treatment in a randomized and placebo-controlled study of generalized MG. 38 Further B-cell directed therapies are under development or have already been approved for other B-cell mediated autoimmune diseases. 35 , 37 …”
Section: B-cell Directed Therapiesmentioning
confidence: 91%
See 3 more Smart Citations
“… 35 Belimumab, a human monoclonal IgG1λ ab directed against B-lymphocyte stimulator (called BLyS, BAFF or TNFSF13B), induces a reduction in B-cell differentiation and thereby leads to a reduced number of circulating CD 19 cells. 37 However, this drug did not show a significant positive effect as adjunctive treatment in a randomized and placebo-controlled study of generalized MG. 38 Further B-cell directed therapies are under development or have already been approved for other B-cell mediated autoimmune diseases. 35 , 37 …”
Section: B-cell Directed Therapiesmentioning
confidence: 91%
“… 37 However, this drug did not show a significant positive effect as adjunctive treatment in a randomized and placebo-controlled study of generalized MG. 38 Further B-cell directed therapies are under development or have already been approved for other B-cell mediated autoimmune diseases. 35 , 37 …”
Section: B-cell Directed Therapiesmentioning
confidence: 91%
See 2 more Smart Citations
“…Iscalimab is an anti-CD40 monoclonal antibody that does not reduce the proportion of B cells but triggers a blockade of T cell-dependent antibody responses. Notably, a double-blind, placebo-controlled, phase II study of gMG and MuSK antibodies demonstrated high levels of safety ( 59 ). Pharmacological studies have shown that the principal mechanisms of these drugs include the reduction of leukocytes or interference with other pathways but not the blockade of the complement system.…”
Section: Potential Alternative Complement-based Treatment Methodsmentioning
confidence: 99%